Survival Following Lung Metastasectomy in Soft Tissue Sarcomas - Giuliano, Katherine; Sachs, Teviah; Montgomery, Elizabeth; Guzzetta, Angela; Brock, Malcolm; Pawlik, Timothy M.; Yang, Stephen C.; Ahuja, Nita (The Thoracic and Cardiovascular Surgeon, 2016)
Background The most common site of metastasis for soft tissue sarcomas (STSs) is the lung. In patients who are candidates for resection, metastasectomy improves survival. Debate remains, however, on approach and patient selection for surgery.Methods We retrospectively analyzed demographics, tumor characteristics, peri- and postoperative factors for 53 patients who underwent lung metastasectomy for STS from 1989 to 2013. Disease-free intervals (DFIs) and survival were determined. Kaplan–Meier estimates and log-rank test were used for comparison and survival analyses.Results Median overall survival (diagnosis to death or last visit) was 59.9 months (IQR: 118.5), with mean follow-up of 85.3 months (SD: 69.5). Post-lung metastasectomy survival was 82.9%, 52.2%, 28.3%, and 13.3% at 1, 3, 5, and 10 years, respectively. Age at diagnosis of less than 50 years (p = 0.037), a low pathologic grade (p = 0.040), and a DFI until metastasis of greater than 13.5 months (p = 0.007) were significant predictors of improved survival.Conclusion Patients diagnosed at a younger age with low-grade tumors and those with a longer DFI prior to metastasis diagnosis gain the greatest survival advantage with surgery.
Keywords: lung cancer treatment; metastases/metastasectomy; sarcoma; thoracoscopy/VATS